2019
DOI: 10.7717/peerj.5894
|View full text |Cite
|
Sign up to set email alerts
|

Putatively asexual chrysophytes have meiotic genes: evidence from transcriptomic data

Abstract: Chrysophytes are a large group of heterotrophic, phototrophic, or even mixotrophic protists that are abundant in aquatic as well as terrestrial environments. Although much is known about chrysophyte biology and ecology, it is unknown if they are sexual or not. Here we use available transcriptomes of 18 isolates of 15 putatively asexual species to inventory the presence of genes used in meiosis. Since we were able to detect a set of nine meiosis-specific and 29 meiosis-related genes shared by the chrysophytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…On theoretical grounds based on the genetic advantages of recombination, it has been argued that most protists are nevertheless likely cryptically sexual at least occasionally (Dunthorn and Katz 2010;Hofstatter and Lahr 2019). And, on experimental grounds, evidence for this cryptic sex throughout the protists has been found by inventorying meiotic genes in different putative asexual lineages (Ramesh et al 2005;Malik et al 2008;Chi et al 2014b;Dunthorn et al 2017;Hofstatter et al 2018;Kraus et al 2018), although these meiotic genes could be used just for selfing or for non-canonical genetic pathways (Dunthorn et al 2017). Sex has, however, been lost in some lineages, some of which could be ancient (Doerder 2014).…”
Section: Sex and Reproduction In Protistsmentioning
confidence: 99%
“…On theoretical grounds based on the genetic advantages of recombination, it has been argued that most protists are nevertheless likely cryptically sexual at least occasionally (Dunthorn and Katz 2010;Hofstatter and Lahr 2019). And, on experimental grounds, evidence for this cryptic sex throughout the protists has been found by inventorying meiotic genes in different putative asexual lineages (Ramesh et al 2005;Malik et al 2008;Chi et al 2014b;Dunthorn et al 2017;Hofstatter et al 2018;Kraus et al 2018), although these meiotic genes could be used just for selfing or for non-canonical genetic pathways (Dunthorn et al 2017). Sex has, however, been lost in some lineages, some of which could be ancient (Doerder 2014).…”
Section: Sex and Reproduction In Protistsmentioning
confidence: 99%
“…The existence of cryptic sexual processes in putative asexuals such as Giardia and Trichomonas was proposed based on testing for the presence of the meiosis‐specific machinery . The same approach was later applied to other putative asexual groups with similar results, but many seemingly asexual lineages remain to be investigated.…”
Section: Meiosis Toolkit Can Reveal the Nature Of Asexual Scandalsmentioning
confidence: 99%
“…Mitotic divisions lead to the liberation of zoospores and would be analogous to vegetative reproduction. Recently, Kraus et al (2019) observed evidence for meiotic or meiosis-related genes based on transcriptomic data, suggesting they are "secretly sexual. "…”
Section: Chrysophyceaementioning
confidence: 99%